Perawatan Paliatif terhadap Kualitas Hidup Pasien Kanker Payudara - Irma Nur Amalia; Mia Listia (Jurnal Keperawatan Silampari, 2020)
This study aims to identify the effect of palliative care on breast cancer patients' quality of life. The method used in this study is a literature review. The results showed that palliative care affected breast cancer patients. In conclusion, comprehensive palliative care from various aspects of the patient's life plays a significant role in achieving the maximum quality of life in breast cancer patients and preparing for a dignified death. Keywords: Breast Cancer, Quality of Life, Palliative Care